Artificial neural network: an upcoming strategic decision planning support tool. (4th August 2014) - Udo, Godwin J.
Finding a reliable technique to help in the strategic planning is not a new research issue. Past studies, using several techniques and models, have shown only limited progress. Existing techniques are either too complex and time–consuming or too unreliable for full–scale adoption. Artificial neural network (ANN) technology seems capable of overcoming most of these shortcomings. This paper overviews existing techniques: the strategic–fit concept, CAPM, traditional DSS, and expert systems and contrasts them with ANN. An illustrative application is used to demonstrate the effectiveness of ANN in supporting a diversification strategic planning.